Histopathological Patterns of Renal Biopsy and their Treatment Outcomes at A tertiary hospital in Dhakka: An Observational Study - Raisa, Fairooz; Rahman, Ebadur; Masum Kamal Khan, Muhammad; Begum, Fahmida; Samad, Tabassum; Alam, SM Mahbub; Khalid, Ahmed; Nazim, Rezoyana; Rahim, Rubiya Rahim; Mahmud, Arif (Pakistan Journal of Kidney Diseases, 2025)
Background: Renal biopsy is the gold standard for diagnosing the underlying cause of renal diseases. It provides critical insights into histopathological patterns, enabling tailored management and prognostic assessment. In this study, we have assessed the histopathological patterns of renal biopsy and their treatment outcome at our tertiary care hospital in Dhakka. Method: This was a retrospective observational study among patients who underwent renal biopsies from June’24 to September’25 (16 months) at department of Nephrology. Result: Total of 60 patients were included in the study. Mean age was 39 (±2) years, with a male to female ratio of 2:3. The most common co-morbidity observed was Hypertension (42%), followed by Diabetes Mellitus (18%). ​Renal biopsy was most frequently indicated for proteinuria (48.33%, 29/60), with Nephrotic Syndrome accounting for 62% (18/29) of these cases. IgANw s the commonset diagnosis followed by FSGS, 26.9% and 15% respectively. ​Complete or partial remission was achieved in 38.3 % of patients at one year. Tubule-interstitial involvement at presentation was associated with a poorer outcome. Conclusion: This study highlights that among our cohort of patients at a tertiary hospital the most frequent diagnosis was IgAN. Complete and partial remission was observed in one third of our patients. It is therefore important to diagnose the GN at an early stage with prompt treatment that may help to improve the clinical outcome of our patients.